Advanced Non–Small Cell Lung Cancer Patients With Low Tumor Mutation Burden Might Derive Benefit From Immunotherapy. Issue 6 (July 2020) - Nie, Wei; Xu, Mi-Die; Gan, Lu; Zhang, Yi; Qian, Jie; Gu, Kai; Zhang, Xue-Yan; Wang, Hui-Min; Yan, Bo; Gu, Ping; Zhang, Bo; Wang, Shu-Yuan; et al.
Abstract : The aim of this study is to investigate the association between tumor mutation burden (TMB) and survival in non–small cell lung cancer (NSCLC) patients with anti-programmed cell death protein 1 and anti-programmed death-ligand 1 blockade. Two retrospective cohorts and The Cancer Genome Atlas NSCLC data set were included in this study. The restricted cubic spline analysis was used to explore the association between TMB and survival. The cutoff values for TMB were determined by X-tile software. Primary outcomes were overall survival (OS). The associations between TMB and intratumor heterogeneity, number of segments, fraction of genome alterations, aneuploidy score, and T-cell populations were also investigated. In the restricted cubic spline plots, TMB showed an inverted U-shaped curve with OS. The median OS in the low TMB group was significantly longer than those in the medium TMB group. In The Cancer Genome Atlas NSCLC data set, low TMB was also associated with longer OS in comparison with medium TMB. Furthermore, NSCLC patients with low TMB had significantly lower intratumor heterogeneity, number of segments, fraction of genome alterations, aneuploidy score, T-helper type 2 (Th2) cells, and CD8 + T cells, but higher levels of Th1 and Th17 cells. Low TMB might be a prognostic factor for NSCLC patients receiving anti-programmed cell death protein 1/programmed death-ligand 1 immunotherapy.